Brewing Jujube Brandy with Daqu and Yeast by Solid‐State Fermentation. Issue 2 (21st May 2015) - Li, Shu‐gang; Mao, Zhi‐yang; Wang, Ping; Zhang, Ye; Sun, Pan‐pan; Xu, Qian; Yu, Jun
Abstract: Chinese J unzao jujube in Xinjiang is a high‐quality brew resource because of its high sugar content. Jujube paste was hydrolyzed by a multi‐enzyme and then fermented with Daqu and yeast through a solid‐state fermentation process. After distilling and aging, the final product has a typical characteristic of brandy. The optimal hydrolysis conditions were a mixture of pectinase and cellulase with a ratio of 1:3, a dosage of multi‐enzyme of 0.75% (w/w), an enzymolysis pH of 3.5–4.0, a temperature of 50C and a time of 3 h. The optimal fermentation process was as follows: active dry wine yeast‐SY yeast strain, dosage of yeast of 0.5%, dosage of Daqu of 18%, fermentation temperature of 25C and fermentation time of 21 days. After distilling and aging, the alcohol content was 51.5% (v/v) and gas chromatography‐mass spectrometry (GC‐MS) analysis demonstrated that the final product has rich, unique flavor characteristics. The results indicated that Daqu and solid‐state fermentation can promote and enrich the flavor formation of jujube brandy. Practical Applications: Jujube output increases rapidly in China, especially in the Xinjiang area, but the development of process technology and high value‐added products of jujube is lacking. The present study provides a new process of brewing brandy with jujube. The results indicated that the enzymatic hydrolysis of raw jujube before fermentation was beneficial for its utilization. The solid‐state fermentation process was feasible for brewing jujube brandy; by combining a mixed strain of yeast and Daqu, a rich flavor of brandy was produced. This process should be a good example for brewing brandy products produced by other types of fruits.